2018
DOI: 10.1080/01612840.2017.1401188
|View full text |Cite
|
Sign up to set email alerts
|

The Transition from University Completion to Employment for Students with Autism Spectrum Disorder

Abstract: A scoping review of articles published from 2000 to 2017 was conducted with the aim to identify what had been discussed and researched related to the transition from completion of university to employment for students with ASD. The review also included identification of published data on the type of degrees studied by university students with ASD. A paucity of discussion and no specific research was identified related to the aims of the review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Our study contributes to the existing literature related to post-secondary transition for individuals with autism (e.g. Cashin 2018;Elias and White 2018;Lambe et al 2019;Vincent 2019Vincent , 2020 by widening the perspective to specifically include students' and graduates' perceptions about employment support related to the transition from university to work. We discovered that the support within university structures was not meeting students' individual needs and that caring relationships were the most favourable supporting factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study contributes to the existing literature related to post-secondary transition for individuals with autism (e.g. Cashin 2018;Elias and White 2018;Lambe et al 2019;Vincent 2019Vincent , 2020 by widening the perspective to specifically include students' and graduates' perceptions about employment support related to the transition from university to work. We discovered that the support within university structures was not meeting students' individual needs and that caring relationships were the most favourable supporting factors.…”
Section: Discussionmentioning
confidence: 99%
“…This period often causes anxiety for those with autism, but it can also be perceived as a positive departure and a moment for identity development when entering adulthood (Vincent 2019). A systematic review by Cashin (2018) found four studies that consisted of a case study, discussion papers, and one UK-based study (Van Hees, Moyson, and Roeyers 2015;MacLeod and Green 2009;Martin 2006Martin , 2007. These studies reported on the importance of individualised support prior, during and beyond the transition from university to the workforce.…”
Section: Autism and Support At Universitymentioning
confidence: 99%
“…Evidence suggests that where transition goals such as these are not met, this can hinder the establishment of viable adult identities among autistic young people and impact negatively on mental health and overall quality of life (Anderson et al 2016;Moss, Mandy and Howlin, 2017;Hendricks and Wehman, 2009). There is, however, a much smaller range of studies that focus on transition for autistic people with higher level qualifications (Bolourian, Zeedyk, and Blacher, 2018;Cashin, 2018;Dipeolu, Storlie, and Johnson, 2015;Walker, 2012;VanBergeijk, Klin and Volkmar, 2008) and there are currently no studies that uncover the firsthand transitional experiences for the increasing population of autistic people exiting university or college. According to Cashin (2018) such a lack of research on educational trajectories among autistic populations is concerning and must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a much smaller range of studies that focus on transition for autistic people with higher level qualifications (Bolourian, Zeedyk, and Blacher, 2018;Cashin, 2018;Dipeolu, Storlie, and Johnson, 2015;Walker, 2012;VanBergeijk, Klin and Volkmar, 2008) and there are currently no studies that uncover the firsthand transitional experiences for the increasing population of autistic people exiting university or college. According to Cashin (2018) such a lack of research on educational trajectories among autistic populations is concerning and must be addressed. Therefore, at an exploratory level, a qualitative research design was deemed appropriate for this study.…”
Section: Introductionmentioning
confidence: 99%
“…The IMAGE project responds to the concerns expressed by autistic students themselves in previous research (see e.g. Cashin, 2018; http://www.autism-uni.org).…”
Section: Contextmentioning
confidence: 99%